MULBERRY CUTTINGS SUBMITTED TO PRE-TREATMENTS WITH WATER AND DIFFERENT ORGANIC SUBSTRATES - GALETI, Naelly Caroline de Souza; CICHELERO, Willian; MUNHOZ, Roxelle Ethienne Ferreira; ZONETTI, Patrícia da Costa (Scientia Agraria, 2010)
The use of different substrates supplemented with organic waste and pre-treatment with water in the development of mulberry cuttings cultivars Miura, SK 1 SK 4 and IZ 6 /2 was evaluated by the present study. Six different treatments were performed: T1 – water pre-treatment and crushed sugar cane substrate, T2 - water pre-treatment and chicken manure substrate; T3 – water pre – treatment without organic residue; T4 - crushed sugar cane substrate; T5 - chicken manure substrate, T6 – substrate with no additional organic waste. Water pre-treatment meant leaving the cuttings immersed in water for a period of 24 hours. The percentage of plants with buds was estimated every two days. After 70 days, the fixation percentage, the daily fixation index (IPD) and the average tillers height were evaluated. The best rooting results were obtained when the cuttings were immersed in water before planting. The crushed sugar cane substrate showed better fixation rates than the chicken manure substrate; however, the plants treated with chicken manure had a better sprout growth. The substrate increased with crushed sugar cane and chicken manure was not shown to be effective in cutting propagation of mulberry.